Dimensões dos arcos dentários de pacientes com e sem anomalias de número, forma e irrupção : estudo em modelos digitalizados - Brandt, Glenda Zaguini (2015)
Dental anomalies may be related to the morphological simplification, that demands dimensional adjustments associated with the orthodontic treatment. This study aims to identify participants with anomalies in quantity, shape and eruption and measure the tooth size and arcades. The sample contained patients in the permanent dentition stage, both genres, that where sampled from the Specialization Course in Orthodontics files in UEM. The anomalies were recorded from the information contained in the documentation, including the radiographies. Were identified dental anomalies in quantity (tooth agenesis), shape conoid tooth), and eruption (ectopic eruption). A group of patients without any anomalies constituted the control group. Both groups were also examined in the Angle classification of malocclusion Angle. The respective casts were scanned by Maestro 3D Scanners, and measured with the help of Ortho Studio program. Data was recorded by a single examiner, being evaluated, tabulated and then submitted to the Student t test with 5% of significance level, testing the null hypothesis that the dimensions do not differ between groups with and without anomalies. In general individuals with dental anomalies decreased the average mesiodistal size and buccolingual as well as the dimensions of the dental arches (P <0.05). Therefore the second premolars and first molars of both arcades, were higher in the group with anomalies (<0.05). Patients with dental anomalies, although show a average and general reduction of tooth size, as well as the dental arches, do not express the simplification in the first molars and especially in the second premolars.